AI application in procurement: prerequisites, use cases, and benefits - Barry, Aaron (My University, 2025)
Artificial intelligence (AI) application in different business functions has increased significantly in recent years. Although evident in procurement as well, AI application has been slower in procurement compared to other areas of business. However, the relatively small amount of academic literature on the topic does identify potential for AI application in procurement and in assisting the function in transitioning from being reactive to proactive. Relatively speaking, however, there is still not enough empirical data on how procurement functions are utilizing AI. This thesis aims to study both present-day and near-future AI application in procurement within large Nordic corporations. This qualitative study has been conducted by interviewing procurement professionals from large Nordic corporations. It aims to study the prerequisites for AI application in procurement, AI use cases in procurement, as well as both experienced and expected benefits of AI application in procurement. The findings indicate that AI application in procurement is still at an early stage. In many cases, application is experimental, often pilot-based. Large language models (LLMs), such as Copilot and ChatGPT, are used to support buyers’ tasks regarding supply market analysis, contract clause comparison, as well as general decision-making, which managers should consider as entry points for AI application. Moreover, specialized AI tools, such as Sievo for spend classification and Celonis for compliance monitoring, are used to automate both data- and knowledge-intensive processes prone to human error. However, respondents note that AI outputs are not always infallible and thus often need a professional to validate them. Overall benefits experienced from AI application in procurement include time savings, improved efficiency, and quality improvements. Currently, AI in procurement focuses more on augmenting human work than replacing it.

Viime vuosina, tekoälyn (AI) hyödyntäminen eri liiketoimintafunktoissa on lisääntynyt merkittävästi. Verratessa sen hyödyntämisen tasoa muihin liiketoimintafunktioihin, sen käyttö hankinnassa on kuitenkin vielä varhaisessa vaiheessa. Tähän asti melko rajallinen määrä aiheeseen liittyvää akateemista kirjallisuutta kuitenkin tuo esiin tekoälyn potentiaalin siirtää hankintaosastojen roolia reaktiivisuudesta proaktiivisuuteen. Empiiristä tietoa siitä, miten yritykset tällä hetkellä hyödyntävät tekoälyä, on kuitenkin vielä rajallisesti. Tämä Pro Gradu -tutkielma tarkastelee AI:n soveltamista tänä päivänä ja lähitulevaisuudessa analysoimalla sen hyödyntämistä pohjoismaisten suuryritysten hankinnassa. Kvalitatiivinen tutkimus toteutettiin haastattelemalla useiden pohjoismaisien suuryritysten hankintajohtajia ja -asiantuntijoita. Tutkimus tarkastelee tekoälyn soveltamiseen liittyviä edellytyksiä, käyttötapauksia sekä saavutettuja hyötyjä hankinnassa. Tutkimuksen tulokset indikoivat, että AI:n hyödyntäminen hankinnassa on vielä varhaisessa vaiheessa. Monessa tapauksessa, implementointi on alustavaa ja kokeilevaa sekä käyttötapauskohtaista. Suuria kielimalleja, kuten Copilot Prota ja ChatGPT:tä, käytetään muun muassa tukemaan markkina-analyysia, sopimuslausekkeiden vertailua sekä yleistä päätöksentekoa. Nämä chatbotit vähentävät aikaa, jota muuten käytettäisiin tiedonhakuun ja muihin rutiinitehtäviin. Erikoistuneemmat ratkaisut, kuten kulutusluokitteluun käytettävä Sievo ja sopimusnoudattamisen seurantaan käytettävä Celonis taas hyödyttävät automatisoimalla hankintaan liittyviä dataintensiivisiä prosesseja sekä vähentämällä inhimillisiä virheitä. Keskusteluissa hankintaosaajien kanssa tuli kuitenkin ilmi, että näiden ratkaisujen tuottamat tulokset vaativat edelleen ihmistä tarkastamaan, että ne menevät oikein. Kokonaisuudessaan, AI:sta koetut hyödyt liittyvät ajansäästöön, tehokkuuden paranemiseen sekä laadun kohentumiseen. Hankintatoimessa AI kuitenkin toimii edelleen ensisijaisesti ihmistyön tukena.
Keywords: artificial intelligence (AI), procurement, strategic purchasing, sourcing, supply, use case, AI application, prerequisite